2012
DOI: 10.1371/journal.pone.0034712
|View full text |Cite
|
Sign up to set email alerts
|

Spiroindolines Identify the Vesicular Acetylcholine Transporter as a Novel Target for Insecticide Action

Abstract: The efficacy of all major insecticide classes continues to be eroded by the development of resistance mediated, in part, by selection of alleles encoding insecticide insensitive target proteins. The discovery of new insecticide classes acting at novel protein binding sites is therefore important for the continued protection of the food supply from insect predators, and of human and animal health from insect borne disease. Here we describe a novel class of insecticides (Spiroindolines) encompassing molecules th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 38 publications
2
49
0
Order By: Relevance
“…For example, Ibutamoren (MK-677, L-163,191) is a potent, orally active growth hormone secretagogue that mimics the stimulating action of the endogenous hormone ghrelin [158,159]. Some spiro[indoline-3,4 -piperidines] have been identified as vesicular acetylcholine transporters (Fig.…”
Section: Synthesis Of 3-spiroindolinones Spiro-fused With Piperidine mentioning
confidence: 99%
“…For example, Ibutamoren (MK-677, L-163,191) is a potent, orally active growth hormone secretagogue that mimics the stimulating action of the endogenous hormone ghrelin [158,159]. Some spiro[indoline-3,4 -piperidines] have been identified as vesicular acetylcholine transporters (Fig.…”
Section: Synthesis Of 3-spiroindolinones Spiro-fused With Piperidine mentioning
confidence: 99%
“…New analogues, which may provide some useful information for future design of new insecticides to dramatically reduce reaction time, increase product yields and enhance product purities by reducing unwanted side reactions . By analyzing the data, we found that all the designed analogues have better insecticidal performance than fipronil and SYN351 . Most of our designed analogues exhibited excellent insecticide activities against Nilaparvata lugen and A .…”
Section: Resultsmentioning
confidence: 87%
“…Even though these chemicals have brought with them undesired environmental and health problems, they are being used extensively 28 29 30 31 . Similarly, the recently introduced Diamides, found effective on various pests, acts on the ryanodine receptor of nervous system 32 33 34 . Since the pests continue to evolve resistance to the various compounds which are currently in use, an effective new alternative compound is in urgent need 7 35 36 .…”
Section: Discussionmentioning
confidence: 99%